EFISIENSI TEKNIS USAHA TANI PADI PETANI PESERTA DAN PETANI NONPESERTA PROGRAM SL-PTT DI KABUPATEN SUKABUMI - Fuji Lasmini; Rita Nurmalina; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The objectives of this study were to analyze the influence of farmers’ participation in SL-PTT rice program on the technical efficiency of farm businesses run by the farmers. The measurement of technical efficiency was conducted by using Data Envelopment Analysis (DEA) oriented toward the inputs of 35 SL-PTT rice program participants and 35 non-participant farmers of SL-PTT rice program in Cisaat District of Sukabumi Regency, particularly during the harvest season III in 2014. The significant difference of the mean value of technical efficiency between the participant farmers and non-participant farmers of SL-PTT rice program was examined by using t-test (different test). The results show that the average value of technical efficiency for all respondents is 0,83. The average value of the technical efficiency of the participant farmers in SL-PTT rice program (0,84) is higher than that of the non-participant farmers in SL-PTT rice program (0,82). The t-test results also show that the values of technical efficiency between both types of farmers are not significantly different. The development of SL-PTT program can be achieved by improving the delivery methods on the PTT technological information to the participant farmers i.e. by involving farmers who hold a role as progressive farmers to convey information and advice to other farmers.Keywords: rice production, SL-PTT of rice, technical efficiency, DEA